Customer Relationship Management Strategies for Improving the Utilization of E-Marketing Operations by Small and Medium Enterprises in South-East, Nigeria - Alonta, G. C.; Obi, O. C.; Orabueze, M. C. (Journal of Research in Adult and Continuing Education, 2024)
This study investigated customer relationship management (CRM) strategies for improving the utilization of e-marketing operations among small and medium scale enterprises (SMEs) in South-East, Nigeria. A single research question guides the study, alongside two null hypotheses were formulated. Employing a descriptive survey research design, data collection takes place across the five states of South-East, Nigeria, encompassing a population of 13,035 registered SMEs. Utilizing a 9-item questionnaire, the study undergoes face validity and reliability testing through the Cronbach Alpha method, yielding a reliability coefficient of 0.82. Descriptive statistics, including mean and standard deviation, are employed for data analysis, with t-test statistics used to test the null hypotheses at 0.05 alpha level. The result indicates that CRM strategies including creating a customer-centric business environment, rewarding loyal customers, personalizing interactions, and ensuring consistent and engaging customer experience effectively enhance the utilization of e-marketing operations in SMEs in South-East, Nigeria. Consequently, it is concluded that SMEs can adopt CRM strategies to improve e-marketing utilization in the region. Recommendations include prioritizing customer needs and ensuring professionalism and ethical conduct among personnel responsible for customer relations.